Antecedents and Consequences of Outward Emotional Reactions in Table Tennis - Fritsch, Julian; Finne, Emily; Jekauc, Darko; Zerdila, Diana; Elbe, Anne-Marie; Hatzigeorgiadis, Antonis (Frontiers in Psychology, 2020)
The purpose of the present study was to shed light on the behavioral component of emotions by investigating antecedents and consequences of outward emotional reactions during table tennis competitions. With regards to the antecedents of outward emotional reactions, in line with appraisal theories, we considered the importance and the controllability of the situation as two important constructs. Fifteen table tennis matches, involving in total 21 players (7 females) with a mean age of 16.71 (SD = 0.70), were video recorded during the finals of the youth National Championship in Greece. Based on the footage, outward emotional reactions after every point were classified as neutral, positive, or negative. Situational factors in relation to the scoring system, bearing the importance and the controllability of the situation, were formed to assess antecedents of outward emotional reactions. To measure the consequences of outward emotional reactions, the impact on the outcome of the next point was assessed. Generalized linear models with a logit link were computed separately for positive outward emotional reactions after having won a point and negative outward emotional reactions after having lost a point. In general, the results show that while situational factors bearing the importance of the situation could predict positive and negative outward emotional reactions, the effects of situational factors bearing the controllability of the situation were less conclusive. In addition, the results also showed interactive effects between the two constructs for both positive and negative outward emotional reactions. With regard to the consequences of outward emotional reactions, negative and positive outward emotional reactions could not predict the outcome of the next point. To conclude, this study highlights the behavioral component of emotions as a viable alternative to enhance our understanding of the role of emotions in sport.